CONDITIONS OF POCKET FORMATION IN THE OKTYABRSKAYA TOURMALINE-RICH GEM PEGMATITE (THE MALKHAN FIELD, CENTRAL TRANSBAIKALIA, RUSSIA) - Peretyazhko I.S.; Zagorsky V.Ye.; Smirnov S.Z.; Mikhailov M.Y. (My University, 2004)
Coexisting melt (MI), fluid-melt (FMI) and fluid (FI) inclusions in quartz from the Oktaybrskaya pegmatite, central Transbaikalia, have been studied and the thermodynamic modeling of PVTX-properties of aqueous orthoboric-acid fluids has been carried out to define the conditions of pocket formation. At room temperature, FMI in early pocket quartz and in quartz from the coarse-grained quartz–oligoclase host pegmatite contain crystalline aggregates and an orthoboric-acid fluid. The portion of FMI in inclusion assemblages decreases and the volume of fluid in inclusions increases from the early to the late growth zones in the pocket quartz. No FMI have been found in the late growth zones. Significant variations of solid/fluid ratios in the neighboring FMI result from heterogeneous entrapment of coexisting melts and fluids by a host mineral. Raman spectroscopy, SEM EDS and EMPA indicate that the crystalline aggregates in FMI are dominated by mica minerals of the boron-rich muscovite–nanpingite CsAl2[AlSi3O10](OH,F)2 series as well as lepidolite. Topaz, quartz, potassium feldspar and several unidentified minerals occur in much lower amounts. Fluid isolations in FMI and FI have similar total salinity (4–8 wt.% NaCl eq.) and H3BO3 contents (12–16 wt.%). The melt inclusions in host-pegmatite quartz homogenize at 570–600 °C. The silicate crystalline aggregates in large inclusions in pocket quartz completely melt at 615 °C. However, even after those inclusions were significantly overheated at 650±10 °C and 2.5 kbar during 24 h they remained non-homogeneous and displayed two types: (i) glass+unmelted crystals and (ii) fluid+glass. The FMI glasses contain 1.94–2.73 wt.% F, 2.51 wt.% B2O3, 3.64–5.20 wt.% Cs2O, 0.54 wt.% Li2O, 0.57 wt.% Ta2O5, 0.10 wt.% Nb2O5, 0.12 wt.% BeO. The H2O content of the glass could exceed 12 wt.%. Such compositions suggest that the residual melts of the latest magmatic stage were strongly enriched in H2O, B, F, Cs and contained elevated concentrations of Li, Be, Ta, and Nb. FMI microthermometry showed that those melts could have crystallized at 615–550 °C.Crystallization of quartz–feldspar pegmatite matrix leads to the formation of H2O-, B- and F-enriched residual melts and associated fluids (prototypes of pockets). Fluids of different compositions and residual melts of different liquidus–solidus P–T-conditions would form pockets with various internal fluid pressures. During crystallization, those melts release more aqueous fluids resulting in a further increase of the fluid pressure in pockets. A significant overpressure and a possible pressure gradient between the neighboring pockets would induce fracturing of pockets and “fluid explosions”. The fracturing commonly results in the crushing of pocket walls, formation of new fractures connecting adjacent pockets, heterogenization and mixing of pocket fluids. Such newly formed fluids would interact with a primary pegmatite matrix along the fractures and cause autometasomatic alteration, recrystallization, leaching and formation of “primary–secondary” pockets.
Keywords: tourmaline